The Professional Identity and Career Attitude of Chinese Medical Students During the COVID-19 Pandemic: A Cross-Sectional Survey in China - Yang, Xingjie; Gao, Lan; Zhang, Suoyuan; Zhang, Libin; Zhang, Ligang; Zhou, Shuangjiang; Qi, Meng; Chen, Jingxu (Frontiers in Psychiatry, 2022)
Background Although professional identity is a strong predictor of career choice, only a few studies have reported on medical students' career attitude during a public health emergency. This study investigates the changes in medical students' professional identity and career attitude during the COVID-19 pandemic, evaluates their mental health and social support system under stress, and explores the relationship between their career attitude and other factors. Methods An online survey of 6,226 Chinese medical students was conducted to collect information on demographics, professional identity, and career attitude. The collected data were assessed using the Patient Health Questionnaire, the Generalized Anxiety Disorder Scale, and the Social Support Rating Scale. Results The results revealed that most (80.8%) of the participants did not change their career attitude and the professional identity of most participants strengthened, and they preferred to participate on the frontline during the COVID-19 pandemic. The prevalence of depression and anxiety among medical students was 22.86% and 35.43%. Low social support, depressive symptoms, male gender, and higher grades were factors that negatively affected career attitude. Conclusions After the outbreak of the pandemic, it was necessary to conduct diversified professional identity research to support medical students, especially those with low social support and depressive symptoms.